Legal maxims and Islamic financial transactions: A case study of mortgage contracts and the dilemma for Muslims in Britain - Zakariyah, Luqman (Brill Academic Publisher, 2012)
This article aims to focus on legal maxims related to financial transactions to explore whether they offer any solutions for Muslims concerned with this dilemma, and to investigate how such legal maxims can be used to shape the way in which Muslims in the West perceive today’s mortgage issues. Some questions raised are the following. When entering a mortgage contract, does a Muslim’s intention change the ruling of the transaction under the pretext of the two maxims al-ʿumūr bi maqāṣidihā (“matters considered according to intention”) and hal al-ʿibrah fī l-ʿuqūd bi l-maqāṣid wa l-maʿanī aw bi l-alfāẓ wa l-mabānī (“in contracts, is effect given to intention and the meaning or expression and form”)? Can one be certain that mortgages are completely ḥarām (unlawful) when considering the maxim al-yaqīn lā yazūl bi l-shakk (“certainty cannot be repelled by doubt”)? What aspects of ḥarām are found in mortgages and can they be marginalized by the maxim al-ḍarūrāt tubīh al-maḥẓūrāt (“necessity makes the unlawful thing lawful”)? If Islam allows bayʿ al-istiṣnāʿ (contract for manufacture) on the basis of ʿurf (custom), can mortgages also be permitted under the maxim al-ʿādah muḥakkamah (“custom is authoritative”)?